Amyloid beta inhibits olfactory bulb activity and the ability to smell. - Reynaldo Alvarado-Martínez (Public Library of Science (PLoS), 2013)
Early olfactory dysfunction has been consistently reported in both Alzheimer's disease (AD) and in transgenic mice that reproduce some features of this disease. In AD transgenic mice, alteration in olfaction has been associated with increased levels of soluble amyloid beta protein (Aβ) as well as with alterations in the oscillatory network activity recorded in the olfactory bulb (OB) and in the piriform cortex. However, since AD is a multifactorial disease and transgenic mice suffer a variety of adaptive changes, it is still unknown if soluble Aβ, by itself, is responsible for OB dysfunction both at electrophysiological and behavioral levels. Thus, here we tested whether or not Aβ directly affects OB network activity in vitro in slices obtained from mice and rats and if it affects olfactory ability in these rodents. Our results show that Aβ decreases, in a concentration- and time-dependent manner, the network activity of OB slices at clinically relevant concentrations (low nM) and in a reversible manner. Moreover, we found that intrabulbar injection of Aβ decreases the olfactory ability of rodents two weeks after application, an effect that is not related to alterations in motor performance or motivation to seek food and that correlates with the presence of Aβ deposits. Our results indicate that Aβ disrupts, at clinically relevant concentrations, the network activity of the OB in vitro and can trigger a disruption in olfaction. These findings open the possibility of exploring the cellular mechanisms involved in early pathological AD as an approach to reduce or halt its progress.